Blockchain for local communities: an exploratory review of token economy aspects - Domenicale, Irene; Viano, Cristina; Schifanella, Claudio (Frontiers in Blockchain, 2024)
Blockchain for local communities are blockchain-based applications that support the participation of people in the social and economic life of their local community. These applications leverage tokenization to enable socioeconomic processes involving transactions of values where community members take part actively and intentionally. In this field, mechanisms that regulate the functioning of blockchains need to be redirected towards collaborative and social purposes that often differ from the logics on which mainstream cryptocurrencies are based. In order to redesign these mechanisms, sound examination of their system of tokenization and of dynamics of their token economy is required. This paper provides an exploratory review of token economy elements found within cases of blockchain for local community economies, which is an under-explored domain in the relevant literature. The analysis considers 9 projects for systems that incentivize or reward participation, or implement community currency schemes. The dimensions analyzed encompass the type of goals and communities, the blockchains adopted, and token economy design aspects such as: token types, their distribution and incentive mechanisms, the associated platform/wallet functionalities, and the project governance models.We have observed a variety of combinations of these elements being used to facilitate new forms of value circulation. However, there is a tension between the aspiration to introduce transformative systems and the need to ensure the stability of the economic framework. The highly experimental nature of these initiatives requires continuous monitoring of their emergence and development.